Consumer Awareness about E-Waste in Rural and Urban Haryana - DHULL, RAHUL; SHRESHTHA, DR. MANI (The journal of contemporary issues in business and government, 2021)
The electronic industry is on the rise across the world and India is no exception to it. The consumer craving for newer and better electronic devices has led to faster rate of obsolescence of such electronic items. The obsolete electronic items, once they reach their end of life stage, need to be discarded and treated as Electronic Waste or E-Waste. E-Waste has surfaced as a major issue due to multifold increase in its quantity in last decade. Similar trends have been observed in India. The State of Haryana being a host to IT and ITes sector is also contributing in generation of larger quantities of E-Waste. The paper attempts to check the level of consumer awareness about E-Waste on five parameters namely: nomenclature, visual, conceptual, causal and general awareness. The study aimed at finding whether any variation exists in the awareness level of rural and urban consumers of Haryana regarding E-Waste. Data has been collected from rural and urban users of electronic products. Data has been analyzed using descriptive statistical tools. The study depicted that though the overall awareness of consumers of electronic items is on the lower side, the awareness of urban respondents is slightly better than the respondents from rural background. The paper also proposes ways and means for the policy makers and implementers to increase the awareness among users of electronic products in Haryana.